ANALISIS STRATIGRAFI DAN RUMUSAN SEJARAH GEOLOGI DAERAH LIMBATO DAN SEKITARNYA, KABUPATEN GORONTALO UTARA, PROVINSI GORONTALO - Mohamad Riski Rahman; Ahmad Zainuri; Intan Noviantari Manyoe (Jurnal Azimut, 2019)
Regionally, the research area is composed of volcanic and plutonic rocks. Stratigraphic data of the study area are still regional scale. This study aims to analyze detailed stratigraphic data and formulate the geological history of the Limbato area and its surroundings. The area located at coordinates 0Âº56â€™6â€ - 1Âº0â€™10.8â€ N dan 122Âº5â€™56.4â€ - 122Âº9â€™10.8â€ E, the area of the study is around 45 kmÂ². The method used in the research is scientific exploration by conducting a surface geological mapping survey. The geological surface in the form of field data collection and laboratory analysis. Field data in the form of lithology data and laboratory analysis in the form of petrology and petrographic analysis. The stratigraphy of the research area is divided into 4 (four) unofficial units, which are sorted from old to young, namely granodiorite units of Middle Miocene age, volcanic breccia units of Late Miocene to Early Pliocene, andesite units of Middle Pliocene and alluvial units of Holocene age.Stratigraphic analysis of the Limbato area is related to geological history. In the Middle Miocene period subduction formed plutonic rocks that produced granodiorite units, then during the Late Miocene volcanic eruptions resulted in volcanic breccia units. The activity was stopped at the time of the Early Pliocene. After the volcanic activity was stopped, then new magma activity occurred at the time of the Middle Pliocene resulting in an andesite unit. After all rock units have been deposited, an erosion process occurs in older units which results in an alluvial unit.